An Apoptotic Body‐based Vehicle with Navigation for Photothermal‐Immunotherapy by Precise Delivery and Tumor Microenvironment Regulation. (27th November 2022) - Sheng, Shupei; Yu, Xuya; Xing, Guozheng; Jin, Limin; Zhang, Yan; Zhu, Dunwan; Dong, Xia; Mei, Lin; Lv, Feng
Abstract: Tumor precision therapy and preventing tumor recurrence and metastasis are the main challenges to tumor eradication. Herein, an apoptotic body‐based vehicle with imaging navigation is developed for precise tumor delivery and photothermal‐immunotherapy by IR820‐conjugated apoptotic body loaded with R848 nanoparticles. The apoptotic body serves as ammunition stores as well as vehicle drive engines, while IR820 acts as a fluorescence imaging navigation and photothermal controlling system. The apoptotic body vehicle can deliver the ammunition to tumor and achieve deep penetration by macrophage‐hitchhiking. Fluorescence imaging navigation opens a control window for photothermal treatment, followed by photothermal triggering of in situ vaccine formation. Further, CD47 antibody loaded hydrogel strengthens innate and adaptive immunity, simultaneously the polarization of macrophages regulates the immunosuppressive microenvironment to further promote the combined antitumor immunotherapy. With breast tumor (4T1)‐bearing mice model, the apoptotic body vehicle performs excellent therapeutic efficacy for primary tumor, distant tumor, tumor metastasis, and recurrence prevention. Abstract : An apoptotic body vehicle with imaging navigation is successfully engineered by encapsulating fluorescent photothermal agent IR820 and R848 nanoparticles into apoptotic body. The apoptotic body vehicle performs excellent therapeutic efficacy with aCD47/GEL for primary tumor, distant tumor, metastasis, and recurrence prevention through inducing the strong immune response of the body and regulating the immunosuppressive microenvironment, which provides a potential strategy for prevention of tumor combination treatment.